Implementing Directives that Involve Prepositions with Children with Autism: A Comparison of Spoken Cues with Two Types of Augmented Input. (June 2013) - Schlosser, Ralf W.; Laubscher, Emily; Sorce, James; Koul, Rajinder; Flynn, Suzanne; Hotz, Lindsy; Abramson, Jennifer; Fadie, Holly; Shane, Howard
Abstract Some children with autism face considerable challenges with comprehension, including difficulties following spoken directives involving prepositional relations. The use of augmented input through visual modalities might be an effective means for supplementing spoken language. The purpose of this preliminary study was to compare spoken input with two augmented input modalities (i.e., speech + visual cues) in terms of children's ability to follow directives involving prepositions. The augmented input modalities consisted of static scene cues (i.e., photographic or pictorial visual scenes that portray relevant concepts and their relationships) and dynamic scene cues (i.e., full-motion video clips that depict the actions underlying relevant concepts and their relationships). A within-subjects design involving nine children with autism or pervasive developmental disorders-not otherwise specified was used to examine the effectiveness of the three input conditions. Results indicated that both static scene cues and dynamic scene cues were more effective than spoken cues, but there were no differences between static scene cues and dynamic scene cues. Results are discussed in terms of appropriate instructional inputs for children with autism. Limitations are noted and directions for future research are posited.